YB1 and its role in osteosarcoma: a review - Wu, Feipeng (Frontiers in Oncology, 2024)
YB1 (Y box binding protein 1), a multifunctional protein capable of binding to DNA/RNA, is present in most cells and acts as a splicing factor. It is involved in numerous cellular processes such as transcription, translation, and DNA repair, significantly affecting cell proliferation, differentiation, and apoptosis. Abnormal expression of this protein is closely linked to the formation of various malignancies (osteosarcoma, nasopharyngeal carcinoma, breast cancer, etc.). This review examines the multifaceted functions of YB1 and its critical role in osteosarcoma progression, providing new perspectives for potential therapeutic strategies.